1990
DOI: 10.1159/000111841
|View full text |Cite
|
Sign up to set email alerts
|

Ganglioside GM1 Elevation in DBA/2 Mouse Embryos

Abstract: The composition of whole embryo gangliosides at embryonic day E-12 was compared among the C57BL/6 (B6) DBA/2 (D2), and C3H mouse strains. N-acetylneuraminic acid was the predominant sialic acid species in the E-12 embryos. N-glycolyneuraminic acid was either undetectable or present in only trace amounts. Whole embryo ganglioside sialic concentration was significantly lower in D2 embryos than in B6 or C3H embryos. GM3 and GD3 were the most abundant ganglioside species in each strain and comprised approximately … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Therefore, it is thought that the GSL expression patterns in the developing mouse brains are regulated mainly by glycosyltransferases, but not by glycosidases. On the other hand, a previous study suggested that the GM1 amount increased in embryos of DBA/2 mice, exhibiting reduced β‐galactosidase activity (Bouvier and Seyfried 1990). We do not have a satisfactory explanation as to this anomaly.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, it is thought that the GSL expression patterns in the developing mouse brains are regulated mainly by glycosyltransferases, but not by glycosidases. On the other hand, a previous study suggested that the GM1 amount increased in embryos of DBA/2 mice, exhibiting reduced β‐galactosidase activity (Bouvier and Seyfried 1990). We do not have a satisfactory explanation as to this anomaly.…”
Section: Discussionmentioning
confidence: 93%
“…In human and mouse, the two lysosomal ␤-galactosidases, galactosylceramidase (GALC) and acid ␤-galactosidase (BGAL), share substrate specificity to degrade lactosylceramide (Tanaka and Suzuki, 1976). It is known that tissue activities of acid ␤-galactosidase vary in different strains of mice (Felton et al, 1974;Bouvier and Seyfried, 1990). This factor might be responsible for lactosylceramide accumulation in the brain of twitcher mice on the mixed background.…”
Section: Discussionmentioning
confidence: 99%